Usability testing of HRMIS / Siti Ubaidah Yusuf - Yusuf, Siti Ubaidah (2014)
There is no doubt that internet has changed the way people communicate. Due to this, Malaysian government has taken an initiative implementing the electronic government (e-Government) to improve the services between the government and citizens by using the Internet, at the same time, reduce the operational cost in back office and IT. One of the Malaysian e-Government projects is HRMIS. HRMIS would link all Government agencies electronically, and aims to standardizing human resources practices in the federal government, state government, statutory bodies and local authority services. Even though, the government has promoted the usage of HRMIS, the adoption rate among government servant is still low. There are few researches done on HRMIS before but none of them are focusing on usability testing. The purpose of the study is to investigate the usability problem of HRMIS and provide suggestion according to usability problems on finding. The method used in this study is usability testing with 5 participants which involved with actual task. The testing was held in Usability Lab at Faculty of Computer and Mathematical Sciences, UiTM Shah Alam. From the finding, there are some consideration needs to be taken for system improvement such as menu structure, screen management, the usage of graphic and icons and error handling. The result of this study will contribute for future research on usability testing in Malaysia.